Community Multiculturalism in Pematangsiantar City: Ethnicity, Religion and Culture - Siburian, Eric Sapetra; Sinurat, Anggiat; Haloho, Bongguk (JUPE : Jurnal Pendidikan Mandala, 2023)
Pematangsiantar City as one of the cities in Indonesia with a multicultural society. Pematangsiantar City is a stopover city located in the middle of Simalungun district which has a cultural slogan "Sapangambei Manoktok Hitei" which can be interpreted in general as "Working together to achieve common goals". The slogan is meaningful as a reflection of the people of Pematangsiantar whose background consists of various tribes, religions and cultures who can work together to achieve common goals with the values of togetherness, tolerance and mutual respect for one another in differences. The results of the research using descriptive qualitative methods from several sources of literature show that the people of the city of Pematangsiantar as a multicultural and complex society can carry out the values of this multicultural society with the state philosophy of Pancasila. All elements in the city of Pematangsiantar both from social organizations, religious organizations and youth organizations can work together to achieve common goals and mutually maintain the values of difference and diversity in a multicultural society